Factors of social media influencer on online purchase intention among generation Z - Soong, Vai Ven (2023)
The Objective of this research is to investigate the factors of social media influencer on online purchase intention among generation z. Factors such as perceived trust, perceived expertise, perceived credibility and parasocial relationships, and is there a relationship between these factors to online purchase intention among gen z.